Pernikahan Beda Keyakinan Menurut I Korintus 7:12-16 dan Relevansinya dalam Pluralitas Agama di Indonesia - Dharmawan, Rinaldi; Hermanto, Yanto Paulus; Simanjuntak, Ferry (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2022)
Amid a pluralistic Indonesian society in terms of religion, interfaith marriage has the potential to occur. But until now, interfaith marriage is still being debated among Christians. The Apostle Paul in 1 Cor 7:12-16 states the prohibition to divorce unbelieving spouses. The research aims to explore the meaning of the prohibition on divorcing non-believing spouses and its relevance to Christians in Indonesia. The method used is a qualitative approach to literature study. The results of the study show that: 1) Paul's prohibition on divorcing unbelieving spouses is due to the belief that the process of sanctification of unbelieving partners can occur in marriage; 2) concerning marriage, the main thing is the creation of peace; 3) Paul's teachings are very relevant to be applied among Christians in Indonesia in the form of acceptance of interfaith marriages, which can also be seen as part of the realization of peace.